DNA fragmentation of sperm: a radical examination of the contribution of oxidative stress and age in 16 945 semen samples. Issue 10 (8th September 2020) - Vaughan, D A; Tirado, E; Garcia, D; Datta, V; Sakkas, D
Abstract: STUDY QUESTION: What is the relationship between sperm DNA fragmentation and oxidative stress (OS) with increasing male age? SUMMARY ANSWER: Sperm DNA fragmentation increases with age and is likely related to both defective spermatogenesis and increasing OS levels. WHAT IS KNOWN ALREADY: Sperm quality declines with age. The presence of DNA damage in a high fraction of spermatozoa from a raw semen sample is associated with lower male fertility in natural conception and intrauterine insemination. STUDY DESIGN, SIZE, DURATION: A retrospective cohort study of 16 945 semen samples analysed at a single reference laboratory between January 2010 and December 2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: All males were undergoing an infertility evaluation. The cohort was divided into seven age categories: <30, 30–34, 35–39, 40–44, 45–49, 50 to <54 and ≥55 years. The mean age was 37.6 years (SD 6.8). Sperm DNA fragmentation index (DFI) and high DNA stainability (HDS) were calculated using flow cytometry. OS levels were measured using the oxidative stress adducts (OSA) test, by spectrophotometry. ANOVA with weighted polynomial contrast analysis was used to evaluate trends for DFI, OSA and HDS values across age categories. MAIN RESULTS AND THE ROLE OF CHANCE: Mean DFI significantly increased across all age groups ( P trend  < 0.001). OSA was lowest in patients <30 years old (mean 3.6, SD 1.0) and also increased as age increased ( P trend  < 0.001). There was a statistically significant difference between age groups for each of the three parameters ( P  < 0.001). There was a significant linear trend for DFI, OSA and HDS across the seven age categories ( P  < 0.001). Among patients with high DFI, there was a decreasing age-dependent trend in the patients observed with high OSA ( P  < 0.001). LIMITATIONS, REASONS FOR CAUTION: This is a retrospective study. All males included in the study were undergoing a work-up for infertility and may not be representative of a fertile population. Additional patient demographics and clinical data were not available. WIDER IMPLICATIONS OF THE FINDINGS: DNA and/or oxidative damage in sperm may be just as important to understand as the chromosomal aberrations that are carried in the oocyte. Further studies are needed to evaluate the effect of advancing paternal age on the male genome and, ultimately, on the health of the offspring. STUDY FUNDING/COMPETING INTEREST(S): No funding was obtained for this study. V.D. is an employee of Reprosource/Quest Diagnostics. D.S. reports he was a Scientific Advisor to Cooper Surgical. TRIAL REGISTRATION NUMBER: N/A